Employee Competence Development Needs at The Office of Education and Culture of Enrekang Regency - Sulfia, Sulfia; Ansar, Ansar; Arnidah, Arnidah (Universitas Negeri Makassar, 2025)
Abstract.This study aims to analyze the competency development needs of employees at the Education and Culture Office of Enrekang Regency. The research focuses on five aspects of competency: knowledge, skills, self-concept and values, personal characteristics, and motivation. A qualitative descriptive approach was employed, utilizing data collection techniques such as in-depth interviews, observation, and documentation. Informants included the head of the office, planning sub-section head, supervisors, and staff. The findings indicate that most employees possess sufficient basic understanding and skills to carry out their duties and responsibilities. However, there remains a need to enhance competencies in areas such as information technology proficiency, understanding of the latest policies, and skills in educational program planning and evaluation. Supporting factors include the availability of training and the employees’ commitment to continuous learning, while inhibiting factors include limited training facilities and mismatches between educational background and job assignments. The office’s efforts to address these needs include conducting regular training and workshops to improve staff competencies. The study recommends a structured, sustainable, and needs-based strategy for competency development.